PENGEMBANGAN TEORI DAN PRAKTEK AKUNTANSI SYARIAH DI INDONESIA - Hidayah, Widyatul (UIN Sumatera Utara, 2023)
The practice of sharia accounting which is often known as sharia accounting recognizes Indonesia's progress in the field of accounting. The sharia concept in accounting is a reflection of Islamic teachings, which have an impact on all parts of human life, including economic and accounting concepts. The dynamics of the development of sharia accounting theory is in line with the socio-economic conditions of the Indonesian people, who are predominantly Muslim. This practice is very important to educate the public that sharia accounting is a solution for the Islamic community in obeying and implementing Islamic law. This research uses descriptive qualitative method in its research. Which is the purpose of this study is to explain some important points about the practice and theory of sharia accounting in Indonesia.